2022
DOI: 10.1021/acs.inorgchem.2c01379
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation of Catalytic Water Splitting by the Arene-Anchored Actinide Complexes

Abstract: Actinide complexes, which could enable the electrocatalytic H2O reduction, are not well documented because of the fact that actinide-containing catalysts are precluded by extremely stable actinyl species. Herein, by using relativistic density functional theory calculations, the arene-anchored trivalent actinide complexes (Me,MeArO)3 ArAn (marked as [AnL]) with desirable electron transport between metal and ligand arene are investigated for H2 production. The metal center is changed from Ac to Pu. Electron-spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…The type of chemical bond can be identified based on the QTAIM values. It can be observed that the energy density H ( r ) of the M o –O bond in U i Mo o – O CO is negative, and ρ( r ) > 0, ∇ 2 ρ( r ) > 0, suggesting a dative bond. ,, It is evident that U i Mo o – O CO exhibits larger absolute values than ones of U i Nd o – O CO and U i U o – O CO. This discrepancy suggests a stronger interaction of the Mo o –O bond, that is, Mo o has a stronger ability to adsorb CO 2 .…”
Section: Resultsmentioning
confidence: 91%
“…The type of chemical bond can be identified based on the QTAIM values. It can be observed that the energy density H ( r ) of the M o –O bond in U i Mo o – O CO is negative, and ρ( r ) > 0, ∇ 2 ρ( r ) > 0, suggesting a dative bond. ,, It is evident that U i Mo o – O CO exhibits larger absolute values than ones of U i Nd o – O CO and U i U o – O CO. This discrepancy suggests a stronger interaction of the Mo o –O bond, that is, Mo o has a stronger ability to adsorb CO 2 .…”
Section: Resultsmentioning
confidence: 91%
“…However, conducting experiments is bound to be difficult and contingent, so the use of computational methods can provide the theoretical basis and alternative solutions for experimental studies and avoid many risks. 3 The design and applications of uranyl complexes have been quite extensive, such as studies employing uranyl complexes for the separation of lanthanides and actinides, [4][5][6][7][8][9] the separation of chiral enantiomers, [10][11][12][13][14][15][16] and the removal and extraction of radionuclides. [17][18][19][20] Among them, the separation of chiral enantiomers using uranyl-containing receptors is a promising and valuable study.…”
Section: Introductionmentioning
confidence: 99%